(untitled) (Journal of Imam Al-Kadhim College, 2024)
Abstract: God Almighty created man and created religion for him in order to regulate peoples relationship with each other and regulate their relationship with God Almighty, He Almighty chose for His servants a valuable religion, which He made for all people and sent in it and sent the messenger prophets, so he said what does it mean ’’Indeed, the religion in the sight of Allāh is Islām. And those who were given the Scripture did not differ except after knowledge had come to them - out of jealous animosity between themselves. And whoever disbelieves in the verses of Allāh, then indeed, Allāh is swift in [taking] account. ’’(Āl-‘Imrān19) which is the religion of monotheism that the all of the prophets and messengers, peace be upon them, came about, God Almighty divided this religion that He chose for His servants into different jurisprudenc , so there was Judaism first, then Christianity,and then was sealed with the Islam, Then it concluded with the Islam, which God Almighty singled out for this late nation, and made their Prophet Muhammad, may God bless him and grant him peace, a herald and a warner for all mankind. There was disagreement over whether it was the jurisprudenc of Islam, Whether or not it abrogated the that who came before , some of them denied abrogation in general, and some of them permitted it rationally and denied quoting, and this is what we will show in this research by discussing the evidence and analysis of each group. And from God, success and payment.